Experiences and perspectives regarding challenge-based learning in online sustainability education [version 1; peer review: 1 approved, 2 approved with reservations] - Karin Rebel; Frans Prins; Julia Kasch; Veronique Schutjens; Margien Bootsma; Arjan Kirkels; Frans van Dam (Emerald Publishing, 2022)
In this opinion article, the authors share their experiences with and perspectives on course design requirements and barriers when applying challenge-based learning (CBL) in an online sustainability education setting. CBL is an established learning approach for (higher) sustainability education. It enables teachers to engage students with open, real-life grand challenges through inter-/transdisciplinary student team collaboration. However, empirical research is scarce and mainly based on face-to-face CBL case studies. Thus far, the opportunities to apply CBL in online educational settings are also underinvestigated. Using the TPACK framework, the authors address technological, pedagogical and content knowledge related to CBL and online sustainability education. The integration of the different components is discussed, providing teachers and course designers insight into design requirements and barriers. This paper supports the promising future of online CBL for sustainability education, especially in the context of inter-/national inter-university collaboration, yet emphasizes the need for deliberate use of online collaboration and teaching tools.